Preparation method and application of mesoporous carbon loaded nano metal particle catalyst
Through the preparation of mesoporous carbon-supported nanometal particle catalysts, the problem of existing catalysts being expensive and difficult to recover is solved, and the high-efficiency hydrogen production reaction and cost reduction is achieved, and the catalyst has good magnetic properties and is easy to recover.
Patent Information
- Application Number
- CN202411450421.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-10
AI Technical Summary
The existing hydrogen production catalysts for ammonia borane hydrolysis belong to heterogeneous catalytic processes, which are expensive and difficult to recycle, limiting their industrial applications.
The preparation method of mesoporous carbon-supported nanometallic particles is adopted. By mixing iron salts and fumaric acid in N,N-dimethylformamide, the mesoporous carbon-supported iron nanometers are formed by thermal cracking and hydrogen reduction. The particles were then wrapped with ruthenium atoms under ultrasonic action to prepare a mesoporous carbon-supported ruthenium iron-clad nanoparticle catalyst.
High reaction activity and conversion frequency are achieved, the cost of precious metals is reduced, and the magnetic properties are used to facilitate the recycling of catalysts, thereby improving production efficiency.
Smart Images

Figure CN119281349A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a preparation method of a mesoporous carbon-supported nano-metal particle catalyst and application thereof. Background Art
[0002] Due to the massive consumption of fossil fuels such as petroleum, energy sources are gradually depleted, and human demand for energy is increasing day by day. The development of new energy has become an inevitable trend in social development. Hydrogen energy, as the cleanest energy, is increasingly valued by people. Among hydrogen storage materials, boron nitrogen compounds have received special attention due to their low molecular weight and high hydrogen storage capacity. Under appropriate conditions, ammonia borane can be quickly hydrolyzed to release hydrogen, which is of great significance to the development and utilization of hydrogen energy in my country. Therefore, the development of a highly active and low-cost hydrogen production catalyst is the central theme in the field of new energy.
[0003] The catalysts that promote the rapid release of hydrogen from ammonia borane mainly include precious metal catalysts and non-precious metal catalysts. Although precious metal catalysts show excellent catalytic performance, their resources are scarce, their prices are extremely expensive, and they are not conducive to industrial production applications. Non-precious metal catalysts are simple to synthesize, their resources are relatively abundant, and their costs are relatively low, but their catalytic performance is generally lower than that of precious metal catalysts. In order to be more economically applied to production, the development of an efficient and economical alloy catalyst has become a research hotspot. Precious metal elements such as Ru, Pt and other nanoparticles have good chemical activity and thermal stability, and are important catalysts widely used in the process of ammonia borane hydrolysis and hydrogen production. However, since it belongs to a heterogeneous catalytic process, it is expensive and difficult to recycle. Therefore, by doping with non-precious metal nanoparticles such as Fe and Co, the magnetism of the catalyst is enhanced and the recovery rate of the catalyst is improved. It can act as an active factor and a reducing agent, and can greatly save the cost of precious metals. It is a relatively novel method. To this end, practitioners have designed a preparation method and application of a mesoporous carbon-supported nanometal particle catalyst. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a mesoporous carbon-supported nanometal particle catalyst and its application in order to solve the problem that an important catalyst widely used in the existing ammonia borane hydrolysis hydrogen production process belongs to a heterogeneous catalytic process, is expensive and difficult to recycle.
[0005] The present invention achieves the above-mentioned purpose through the following technical scheme: A method for preparing a mesoporous carbon-supported nano-metal particle catalyst comprises the following steps:
[0006] S01, adding iron salt powder and fumaric acid into N,N-dimethylformamide (DMF), mixing evenly, heating and stirring in an oil bath for 1-2 h to obtain a mesoporous carbon precursor dispersion;
[0007] S02, the mesoporous carbon precursor dispersion in step S01 is fully washed with ethanol and N,N-dimethylformamide (DMF), dried in a vacuum oven, and then fully ground with a mortar to obtain a mesoporous carbon precursor powder (MC);
[0008] S03, placing the mesoporous carbon precursor powder prepared in step S02 into a tubular furnace for thermal cracking to obtain an iron-based mesoporous carbon powder;
[0009] S04, introducing hydrogen into the iron-based mesoporous carbon powder in step S03 in a tube furnace for reduction, so that the iron ions in the iron-based mesoporous carbon precursor are reduced to elemental iron, and a mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) is obtained;
[0010] S05. Add the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and ruthenium chloride powder in step S04 to a mixed solution of deionized water and ethanol, oscillate under the action of ultrasound for 10-30 min, and then stir under mechanical force for 6-8 h. The elemental ruthenium is wrapped on the surface of the iron nanoparticles (FeNPs). Wash away impurities with deionized water and ethanol respectively, and obtain a mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) after rotary evaporation for 2-4 h.
[0011] Furthermore, the iron salt powder in step S01 includes iron nitrate, the molar ratio of the iron salt powder to fumaric acid is 1:(0.2-2), the heating temperature of the oil bath is 90-130° C., and the stirring speed is 200-800 r / min.
[0012] Furthermore, in step S02, the washing times with ethanol and N,N-dimethylformamide (DMF) are more than 3 times, the vacuum oven drying temperature is 80-120° C., and the drying time is 12-24 hours.
[0013] Furthermore, in step S03, the atmosphere for thermal cracking of the mesoporous carbon precursor powder is an inert atmosphere, including nitrogen or argon, the heating rate is 3-15° C. / min, the thermal cracking temperature is 600-900° C., and the thermal cracking time is 0.5-3 h.
[0014] Furthermore, in step S04, the reduction temperature is 300-450° C., the reduction atmosphere is a mixture of hydrogen and inert atmosphere, the volume ratio of hydrogen to inert atmosphere is between 1:(2-4), and the reduction time is 1-3 hours.
[0015] Furthermore, in step S05, the mass ratio of the mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) to the ruthenium chloride powder is between 1:(0.01-0.1), the volume ratio of deionized water to ethanol is between 1:(0.1-1), the content of the mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) and the ruthenium chloride accounts for 0.1-5 wt% of the total content, the power of the ultrasound is 20-80 kHz, the number of cleanings with deionized water and ethanol is more than 3 times, and the rotary evaporation temperature is 45-70°C.
[0016] The application of the mesoporous carbon-supported nanometal particle catalyst prepared by the method described above is as follows: a mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) and deionized water are added into a round-bottom flask, dispersed evenly under the action of ultrasound and connected to a reaction device, ammonia borane powder is dissolved in deionized water, an ammonia borane aqueous solution is added into the round-bottom flask with a syringe, and the reaction rate of ammonia borane hydrolysis to produce hydrogen under the catalyst is recorded according to the scale reading.
[0017] Beneficial effects: The invention has reasonable design, simple and stable structure, strong practicability, and has the following advantages:
[0018] 1. The present invention uses an iron-based mesoporous carbon material with a large specific surface area and high porosity as a precursor, and prepares a multi-scale mesoporous carbon material-loaded binary metal nanoparticle catalyst through hydrogen reduction and direct replacement reaction. The size of the mesoporous carbon material is micrometer-level, and the binary metal nanoparticles are nanometer-level. The prepared binary metal nanoparticles are a coating structure, and the catalytically active noble metal is coated on the surface of the transition metal, and has excellent performance at a low content, which is beneficial to significantly reduce costs in industrial production;
[0019] 2. The mesoporous carbon-supported metal nanoparticle catalyst of the present invention has strong magnetism and can be quickly separated from the reaction mixture under the action of an external magnetic field and can be easily recycled;
[0020] 3. The mesoporous carbon-supported metal nanoparticle catalyst of the present invention has high reaction activity and conversion frequency in the ammonia borane hydrolysis hydrogen production reaction, which greatly shortens the production time and improves the production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the mesoporous carbon precursor prepared in Example 1 of the present invention;
[0022] Figure 2 TEM image of Fe-MC prepared in Example 1 of the present invention;
[0023] Figure 3 This is a high-resolution TEM image of Fe-MC prepared in Example 1 of the present invention;
[0024] Figure 4 This is a SEM image of Ru@Fe-MC prepared in Example 1 of the present invention;
[0025] Figure 5 This is a high-resolution TEM image of Ru@Fe-MC prepared in Example 1 of the present invention;
[0026] Figure 6 This is an element content diagram of Ru@Fe-MC prepared in Example 1 of the present invention;
[0027] Figure 7 The hysteresis loop diagrams of Fe-MC and Ru@Fe-MC prepared in Example 1 of the present invention;
[0028] Figure 8 The pore size distribution diagram of Fe-MC and Ru@Fe-MC prepared in Example 1 of the present invention;
[0029] Fig. 9 This is a schematic diagram of a hydrogen production device using catalytic ammonia borane in the present invention;
[0030] Fig.10 This is a catalytic hydrogen production curve of Fe-MC and Ru@Fe-MC prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0032] Embodiment 1:
[0033] A method for preparing a mesoporous carbon-supported nano-metal particle catalyst comprises the following steps:
[0034] S01. During the experiment, 16 mmol of ferric nitrate and 14 mmol of fumaric acid were first added to the N,N-dimethylformamide (DMF) solution, and after being fully mixed, the mixture was transferred to an oil bath and heated at a constant temperature of 110°C while stirring at 500 r / min for 1.5 h. Finally, a reddish-brown mesoporous carbon precursor dispersion was obtained, which laid the foundation for the subsequent preparation of the catalyst.
[0035] S02. The mesoporous carbon precursor dispersion prepared in S01 was washed five times with ethanol and N,N-dimethylformamide (DMF) solution in a high-speed centrifuge to remove unreacted precursors, solvent residues and impurities to ensure that a pure mesoporous carbon precursor was obtained. Subsequently, the washed sample was transferred to a vacuum drying oven and dried at a constant temperature of 100°C for 16 hours to completely remove residual moisture and solvent to ensure the stability of the material. After taking out the sample, it was finely ground in a mortar to obtain a uniform dry mesoporous carbon precursor powder. The microscopic morphology of the powder was observed by scanning electron microscopy (SEM). The results are as follows: Figure 1 As shown, the mesoporous carbon precursor exhibits a typical spindle structure with a length of about 1.8 μm and an average width of about 1 μm, which indicates that it has good morphological characteristics and a suitable size, which is helpful to improve the performance of subsequent catalysts;
[0036] S03, put the mesoporous carbon precursor powder prepared in S02 into a tube furnace, first introduce nitrogen to fully expel the air in the tube furnace to ensure an inert atmosphere during the subsequent heat treatment process, the ventilation time is 20 minutes, then the temperature is raised to 700°C at a heating rate of 10°C / min and maintained at this temperature for 1 hour to promote the carbonization reaction of the precursor and transform its structure into a stable mesoporous carbon powder (MC). This process effectively improves the electrical conductivity and catalytic performance of the material, laying a solid foundation for subsequent applications;
[0037] S04, put the mesoporous carbon powder (MC) prepared in S03 into a tubular furnace, introduce nitrogen for 20 minutes, fully exclude the air in the tubular furnace to ensure the inertness of the reaction environment, then heat up to 400°C at a heating rate of 10°C / min, and introduce hydrogen at the same time, the volume ratio of hydrogen to nitrogen is 1:3, and maintain for 2 hours. During this process, the iron ions in the mesoporous carbon powder (MC) are reduced to iron element (FeNPs). This reaction significantly improves the catalytic activity of the material. After cooling to room temperature, mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) is obtained. Figure 2 As shown, the mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) retains the spindle structure of the mesoporous carbon precursor, with a length of about 1 μm and a width of about 330 nm. In addition, in high-resolution TEM mode, we can clearly observe that the nanoparticles are evenly distributed on the mesoporous carbon material ( Figure 3 ), further confirming the good dispersibility and composite structure of iron nanoparticles;
[0038] S05. Take 500 mg of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) prepared in S04 and 25 mg of ruthenium chloride powder and add them to a mixture of 40 ml of deionized water and 5 ml of ethanol. The addition of ethanol can enhance the dispersibility of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) in the aqueous solution. Oscillate under the action of 60 kHz ultrasound for 25 minutes and stir at room temperature for 7 hours. In this process, the iron element (Fe NPs) on the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) is the only reducing agent to reduce Ru +3 The Ru element was coated on the surface of the FeNPs, and then washed with deionized water and ethanol for 5 times, and then the Ru@FeNPs were rotary evaporated at 60 °C for 3 h to obtain the mesoporous carbon supported Ru@Fe-MC catalyst. Figure 4 As shown in the figure, the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) retains the spindle structure of the mesoporous carbon precursor, but the roughness is significantly increased. Through high-resolution TEM observation, there are a large number of nanoparticles on the surface of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC), and the distribution is uniform ( Figure 5 ), Figure 6 This is the energy dispersive X-ray image of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC), which contains characteristic peaks of C, Ru, Fe and Cu, indicating that Fe and Ru are successfully embedded in the structure of the mesoporous carbon material. Figure 7 The magnetic properties of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) were measured under a vibrating sample magnetometer. The saturation magnetization values were 177emug -1 and 90 emug -1 , and the coercive values are 87 Oe and 93 Oe, respectively, indicating that both the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and the mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) have strong magnetism. The mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) obtained by coating a layer of Ru on the outer layer of the iron element (Fe NPs) on the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) has stronger magnetism. Figure 8 This is the pore size distribution diagram of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC). The pore size of mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) (8-42 nm) is smaller than that of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) (8-48 nm), indicating that the surface of iron element (Fe NPs) is wrapped by Ru atoms.
[0039] Embodiment 2:
[0040] A method for preparing a mesoporous carbon-supported nano-metal particle catalyst comprises the following steps:
[0041] S01. During the experiment, 16 mmol of ferric nitrate and 3.2 mmol of fumaric acid were first added to N,N-dimethylformamide (DMF) solution, mixed thoroughly, and then transferred to an oil bath. The mixture was heated at a constant temperature of 90 °C and stirred at 200 r / min for 1 h. Finally, a reddish-brown mesoporous carbon precursor dispersion was obtained, which laid the foundation for the subsequent preparation of the catalyst.
[0042] S02. The mesoporous carbon precursor dispersion prepared in S01 was washed three times with ethanol and N,N-dimethylformamide (DMF) solution in a high-speed centrifuge to remove unreacted precursors, solvent residues and impurities to ensure that a pure mesoporous carbon precursor was obtained. Subsequently, the washed sample was transferred to a vacuum drying oven and dried at a constant temperature of 80°C for 12 hours to completely remove residual moisture and solvent to ensure the stability of the material. After taking out the sample, it was finely ground in a mortar to obtain a uniform dry mesoporous carbon precursor powder. The microscopic morphology of the powder was observed by scanning electron microscopy (SEM). The results are as follows: Figure 1 As shown, the mesoporous carbon precursor exhibits a typical spindle structure with a length of about 1.8 μm and an average width of about 1 μm, which indicates that it has good morphological characteristics and a suitable size, which is helpful to improve the performance of subsequent catalysts;
[0043] S03, put the mesoporous carbon precursor powder prepared in S02 into a tube furnace, first introduce nitrogen to fully expel the air in the tube furnace to ensure an inert atmosphere during the subsequent heat treatment process, the ventilation time is 20 minutes, then the temperature is raised to 600°C at a heating rate of 3°C / min and maintained at this temperature for 0.5h to promote the carbonization reaction of the precursor and transform its structure into a stable mesoporous carbon powder (MC). This process effectively improves the electrical conductivity and catalytic performance of the material, laying a solid foundation for subsequent applications;
[0044] S04. Put the mesoporous carbon powder (MC) prepared in S03 into a tubular furnace, introduce nitrogen for 20 minutes, fully exclude the air in the tubular furnace to ensure the inertness of the reaction environment, then heat up to 300°C at a heating rate of 3°C / min, and introduce hydrogen at the same time. The volume ratio of hydrogen to nitrogen is 1:2 and maintained for 1 hour. During this process, the iron ions in the mesoporous carbon powder (MC) are reduced to iron element (FeNPs). This reaction significantly improves the catalytic activity of the material. After cooling to room temperature, mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) is obtained. Figure 2As shown, the mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) retains the spindle structure of the mesoporous carbon precursor, with a length of about 1 μm and a width of about 330 nm. In addition, in high-resolution TEM mode, we can clearly observe that the nanoparticles are evenly distributed on the mesoporous carbon material ( Figure 3 ), further confirming the good dispersibility and composite structure of iron nanoparticles;
[0045] S05. Take 500 mg of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) prepared in S04 and 5 mg of ruthenium chloride powder and add them to a mixture of 40 ml of deionized water and 4 ml of ethanol. The addition of ethanol can enhance the dispersibility of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) in the aqueous solution. Oscillate under the action of 20 kHz ultrasound for 10 minutes and stir at room temperature for 6 hours. In this process, the iron element (FeNPs) on the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) is the only reducing agent to reduce Ru +3 The Ru element was coated on the surface of the iron element (Fe NPs), and then washed with deionized water and ethanol for three times, and then the mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) was obtained after rotary evaporation at 45 °C for 3 h. Figure 4 As shown in the figure, the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) retains the spindle structure of the mesoporous carbon precursor, but the roughness is significantly increased. Through high-resolution TEM observation, there are a large number of nanoparticles on the surface of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC), and the distribution is uniform ( Figure 5 ), Figure 6 This is the energy dispersive X-ray image of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC), which contains characteristic peaks of C, Ru, Fe and Cu, indicating that Fe and Ru are successfully embedded in the structure of the mesoporous carbon material. Figure 7 The magnetic properties of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) were measured under a vibrating sample magnetometer. The saturation magnetization values were 177emug -1 and 90 emug -1 , and the coercive values are 87 Oe and 93 Oe, respectively, indicating that both the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and the mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) have strong magnetism. The mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) obtained by coating a layer of Ru on the outer layer of the iron element (Fe NPs) on the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) has stronger magnetism. Figure 8This is the pore size distribution diagram of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC). The pore size of mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) (8-42 nm) is smaller than that of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) (8-48 nm), indicating that the surface of iron element (FeNPs) is coated by Ru atoms.
[0046] Embodiment three:
[0047] A method for preparing a mesoporous carbon-supported nano-metal particle catalyst comprises the following steps:
[0048] S01. During the experiment, 16 mmol of ferric nitrate and 32 mmol of fumaric acid were first added to the N,N-dimethylformamide (DMF) solution, and after being fully mixed, the mixture was transferred to an oil bath and heated at a constant temperature of 130°C while stirring at 800 r / min for 2 hours. Finally, a reddish-brown mesoporous carbon precursor dispersion was obtained, which laid the foundation for the subsequent preparation of the catalyst.
[0049] S02. The mesoporous carbon precursor dispersion prepared in S01 was washed six times with ethanol and N,N-dimethylformamide (DMF) solution in a high-speed centrifuge to remove unreacted precursors, solvent residues and impurities to ensure that a pure mesoporous carbon precursor was obtained. Subsequently, the washed sample was transferred to a vacuum drying oven and dried at a constant temperature of 120°C for 24 hours to completely remove residual moisture and solvent to ensure the stability of the material. After taking out the sample, it was finely ground in a mortar to obtain a uniform dry mesoporous carbon precursor powder. The microscopic morphology of the powder was observed by scanning electron microscopy (SEM). The results are as follows: Figure 1 As shown, the mesoporous carbon precursor exhibits a typical spindle structure with a length of about 1.8 μm and an average width of about 1 μm, which indicates that it has good morphological characteristics and a suitable size, which is helpful to improve the performance of subsequent catalysts;
[0050] S03, put the mesoporous carbon precursor powder prepared in S02 into a tube furnace, first introduce nitrogen to fully expel the air in the tube furnace to ensure an inert atmosphere during the subsequent heat treatment process, the ventilation time is 20 min, then the temperature is raised to 900 ° C at a heating rate of 15 ° C / min, and maintained at this temperature for 3 hours to promote the carbonization reaction of the precursor and transform its structure into a stable mesoporous carbon powder (MC). This process effectively improves the electrical conductivity and catalytic performance of the material, laying a solid foundation for subsequent applications;
[0051] S04, put the mesoporous carbon powder (MC) prepared in S03 into a tubular furnace, introduce nitrogen for 20 minutes, fully exclude the air in the tubular furnace to ensure the inertness of the reaction environment, then heat up to 450°C at a heating rate of 15°C / min, and introduce hydrogen at the same time, the volume ratio of hydrogen to nitrogen is 1:4, and maintain for 3 hours. During this process, the iron ions in the mesoporous carbon powder (MC) are reduced to iron element (FeNPs). This reaction significantly improves the catalytic activity of the material. After cooling to room temperature, mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) is obtained. Figure 2 As shown in Figure 2, the mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) retains the spindle structure of the mesoporous carbon precursor, with a length of about 1 μm and a width of about 330 nm. In addition, in high-resolution TEM mode, we can clearly observe that the nanoparticles are evenly distributed on the mesoporous carbon material ( Figure 3 ), further confirming the good dispersibility and composite structure of iron nanoparticles;
[0052] S05. Take 500 mg of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) prepared in S04 and 50 mg of ruthenium chloride powder and add them to a mixture of 40 ml of deionized water and 40 ml of ethanol. The addition of ethanol can enhance the dispersibility of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) in the aqueous solution. Oscillate under the action of 20 kHz ultrasound for 30 minutes and stir at room temperature for 8 hours. In this process, the iron element (FeNPs) on the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) is the only reducing agent to reduce Ru +3 The Ru element was coated on the surface of the FeNPs, and then washed with deionized water and ethanol for 6 times, and then the Ru@FeNPs were obtained by rotary evaporation at 70 °C for 4 h. Figure 4 As shown in the figure, the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) retains the spindle structure of the mesoporous carbon precursor, but the roughness is significantly increased. Through high-resolution TEM observation, there are a large number of nanoparticles on the surface of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC), and the distribution is uniform ( Figure 5 ), Figure 6 This is the energy dispersive X-ray image of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC), which contains characteristic peaks of C, Ru, Fe and Cu, indicating that Fe and Ru are successfully embedded in the structure of the mesoporous carbon material. Figure 7 The magnetic properties of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) were measured under a vibrating sample magnetometer. The saturation magnetization values were 177emug -1 and 90 emug-1 , and the coercive values are 87 Oe and 93 Oe, respectively, indicating that both the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and the mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) have strong magnetism. The mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) obtained by coating a layer of Ru on the outer layer of the iron element (Fe NPs) on the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) has stronger magnetism. Figure 8 This is the pore size distribution diagram of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC). The pore size of mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) (8-42 nm) is smaller than that of mesoporous carbon-supported iron nanoparticle powder (Fe-MC) (8-48 nm), indicating that the surface of iron element (FeNPs) is coated by Ru atoms.
[0053] Example 4: Detection of the reaction rate of the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) prepared by the methods of Examples 1 to 3 to produce hydrogen by hydrolysis of ammonia borane
[0054] At room temperature and pressure, 6 mg of the mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) of Examples 1 to 3 was added to 5 ml of distilled water and, after 5 min of ultrasonic treatment at 60 kHz, connected to the Fig. 9 The reaction device shown is a device well known to those skilled in the art and will not be described in detail. Subsequently, 10 ml of ammonia borane aqueous solution (60 mM) was added with a syringe. The timing was started from the first bubble generated. Every 30 seconds, the scale number of the liquid level in the burette was recorded. In addition, mesoporous carbon-supported iron nanoparticle powder (Fe-MC) was used as a comparative sample. The reaction conditions were the same as above. The reaction results are shown in FIG. Fig.10 As shown, after 9.5 min, the molar ratio of ammonia borane consumed by the reaction using the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) as the catalyst of Examples 1 to 3 to the hydrogen produced is close to 3, while the reaction using the mesoporous carbon supported iron nanoparticle powder (Fe-MC) as the catalyst does not release gas within 11 min, indicating that metal Ru is the only active factor for the hydrolysis of ammonia borane to produce hydrogen, and the catalytic activity is relatively high. In addition, since the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) has a relatively high magnetic property, the mesoporous carbon supported ruthenium coated iron nanoparticle catalyst (Ru@Fe-MC) after the reaction can be easily separated from the reaction mixture under the action of the external magnetic field force. The specific test results are shown in the following table:
[0055] Embodiment 2 Embodiment 1 Embodiment 3 Fe-MC First bubble generation time 5min 3min 2min 9min 30s dropper liquid level scale 14.7ml 14.5ml 14.2ml 15ml 60s dropper liquid level scale 14.2ml 14ml 13.8ml 14.9ml Molar ratio of ammonia borane consumed and hydrogen produced in 5 minutes 1.7 2.0 2.2 0 Molar ratio of ammonia borane consumed and hydrogen produced in 10 minutes 2.8 3.0 3.0 0
[0056] It can be seen from the above table that the mesoporous carbon-supported metal nanoparticle catalyst prepared by the method has high reaction activity and conversion frequency in the hydrogen production reaction of ammonia borane hydrolysis.
[0057] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and range of equivalents of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0058] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a mesoporous carbon-supported nanometal particle catalyst, characterized in that , including the following steps: S01, adding iron salt powder and fumaric acid into N,N-dimethylformamide (DMF), mixing evenly, heating and stirring in an oil bath for 1-2 h to obtain a mesoporous carbon precursor dispersion; S02, the mesoporous carbon precursor dispersion in step S01 is fully washed with ethanol and N,N-dimethylformamide (DMF), dried in a vacuum oven, and then fully ground with a mortar to obtain a mesoporous carbon precursor powder (MC); S03, placing the mesoporous carbon precursor powder prepared in step S02 into a tubular furnace for thermal cracking to obtain an iron-based mesoporous carbon powder; S04, introducing hydrogen into the iron-based mesoporous carbon powder in step S03 in a tube furnace for reduction, so that the iron ions in the iron-based mesoporous carbon precursor are reduced to elemental iron, and a mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) is obtained; S05. Add the mesoporous carbon-loaded iron nanoparticle powder (Fe-MC) and ruthenium chloride powder in step S04 to a mixed solution of deionized water and ethanol, and oscillate under the action of ultrasound for 10-30 min, and then stir under mechanical force for 6-8 h. The elemental ruthenium is wrapped on the surface of the iron nanoparticles (Fe NPs). Wash away impurities with deionized water and ethanol respectively, and obtain a mesoporous carbon-loaded ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) after rotary evaporation for 2-4 h.
2. The method for preparing a mesoporous carbon-supported nano-metal particle catalyst according to claim 1, characterized in that: The iron salt powder in step S01 includes iron nitrate, and the molar ratio between the iron salt powder and fumaric acid is 1:(0.2-2). The heating temperature of the oil bath pot is 90-130° C., and the stirring speed is 200-800 r / min.
3. The method for preparing a mesoporous carbon-supported nano-metal particle catalyst according to claim 1, characterized in that: In the step S02, the washing times with ethanol and N,N-dimethylformamide (DMF) are more than 3 times, the vacuum oven drying temperature is 80-120° C., and the drying time is 12-24 hours.
4. The method for preparing a mesoporous carbon-supported nano-metal particle catalyst according to claim 1, characterized in that: In the step S03, the atmosphere for thermal cracking of the mesoporous carbon precursor powder is an inert atmosphere, including nitrogen or argon, the heating rate is 3-15° C. / min, the thermal cracking temperature is 600-900° C., and the thermal cracking time is 0.5-3 h.
5. The method for preparing a mesoporous carbon-supported nano-metal particle catalyst according to claim 1, characterized in that: In the step S04, the reduction temperature is 300-450° C., the reduction atmosphere is a mixture of hydrogen and inert atmosphere, the volume ratio of hydrogen to inert atmosphere is between 1:(2-4), and the reduction time is 1-3 hours.
6. The method for preparing a mesoporous carbon-supported nano-metal particle catalyst according to claim 1, characterized in that: In the step S05, the mass ratio of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) to the ruthenium chloride powder is between 1:(0.01-0.1), the volume ratio of deionized water to ethanol is between 1:(0.1-1), the content of the mesoporous carbon-supported iron nanoparticle powder (Fe-MC) and the ruthenium chloride accounts for 0.1-5 wt% of the total content, the power of the ultrasonic wave is 20-80 kHz, the number of cleanings with deionized water and ethanol is more than 3 times, and the rotary evaporation temperature is 45-70°C.
7. Use of the mesoporous carbon-supported nano-metal particle catalyst prepared by the method according to any one of claims 1 to 6, characterized in that: Mesoporous carbon-supported ruthenium-coated iron nanoparticle catalyst (Ru@Fe-MC) and deionized water are added to a round-bottom flask, dispersed evenly under the action of ultrasound and connected to a reaction device. Ammonia borane powder is dissolved in deionized water, and the ammonia borane aqueous solution is added to the round-bottom flask with a syringe. The reaction rate of ammonia borane hydrolysis to produce hydrogen under the catalyst is recorded according to the scale reading.